2017
DOI: 10.1016/j.anr.2017.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Concept Development of “Nursing Presence”: Application of Schwartz-Barcott and Kim's Hybrid Model

Abstract: Co-constructed interaction underscored the value of the nursing presence as an integral component of caring with humanistic and patient-centered approaches. The findings could help clinical nurses have a better understanding of the nursing presence. Findings also can improve educators' and managers' knowledge for developing and conducting appropriate education strategies and caring activities to facilitate the promotion of nursing presence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(52 citation statements)
references
References 19 publications
0
45
0
3
Order By: Relevance
“…The nurse invokes special competencies such as nurse-patient connection (Watson, 2008: 34;Kostovich, 2012: 169), therapeutic silence (Watson, 2008: 34;Hooper, 2013), nurse-patient sharing of stories and experiences (Kostovich, 2012: 169;Hooper, 2013), appropriate eye contact (Watson, 2008: 34;Kostovich, 2012: 169), respecting life, incorporating patients' values and beliefs in the care plan, promoting patients' growth, avoiding objectifying patients (Watson, 2008: 34), therapeutic touch, attentiveness, smiling, sense of humor, centering, and positive body posture (Kostovich, 2012: 169). These competencies make caring presence an integral aspect of nursing care (Mohammadipour, Atashzadeh-Shoorideh, Parvizy, & Hosseini, 2017). Narratives from participants' experiences in this study show that when the nurses were present in the ward, patients were promptly attended to.…”
Section: Resultsmentioning
confidence: 77%
“…The nurse invokes special competencies such as nurse-patient connection (Watson, 2008: 34;Kostovich, 2012: 169), therapeutic silence (Watson, 2008: 34;Hooper, 2013), nurse-patient sharing of stories and experiences (Kostovich, 2012: 169;Hooper, 2013), appropriate eye contact (Watson, 2008: 34;Kostovich, 2012: 169), respecting life, incorporating patients' values and beliefs in the care plan, promoting patients' growth, avoiding objectifying patients (Watson, 2008: 34), therapeutic touch, attentiveness, smiling, sense of humor, centering, and positive body posture (Kostovich, 2012: 169). These competencies make caring presence an integral aspect of nursing care (Mohammadipour, Atashzadeh-Shoorideh, Parvizy, & Hosseini, 2017). Narratives from participants' experiences in this study show that when the nurses were present in the ward, patients were promptly attended to.…”
Section: Resultsmentioning
confidence: 77%
“…Dossey and Keegan ( 2016 ) argued that powerful healing could be facilitated, even whilst engaging in task-orientated nursing activities, through caring presence. Furthermore, several studies support the finding that patient-centred care is an important principle that underpins caring presence (Kostovich & Clementi 2014 ; Mohammadipour et al 2017 ). Kostovich ( 2012 ) confirmed that both being and doing, the essence of nursing presence, are reflected in individualised care.…”
Section: Findings and Discussionmentioning
confidence: 86%
“…Valuable communication, balance/recovery, and growth and excellence are the main consequences of this concept. [15]…”
Section: Introductionmentioning
confidence: 99%